2016
DOI: 10.1177/1473325016670484
|View full text |Cite
|
Sign up to set email alerts
|

When does compassion fatigue hit social workers? Caring for oncology patients in Korea

Abstract: Understanding compassion fatigue is vital to supporting the health and well-being of oncology psychosocial service providers and oncology patients. This study aims to examine when compassion fatigue is experienced and how it is dealt with by medical social workers providing psychosocial care for oncology patients. A purposeful sample of 12 medical social workers was recruited; each participant was working at a hospital and providing psychosocial care for oncology patients in Korea. Through in-depth qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
(48 reference statements)
2
15
0
1
Order By: Relevance
“…Another influential factor affecting this lack of professional competence is an inability to separate work from home life. The results of this study, in line with other reports show that the effect of unpleasant work experienced by social workers and their inability to manage these experiences had an affect on their personal life and caused burnout (Simon et al, 2005;Yi et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Another influential factor affecting this lack of professional competence is an inability to separate work from home life. The results of this study, in line with other reports show that the effect of unpleasant work experienced by social workers and their inability to manage these experiences had an affect on their personal life and caused burnout (Simon et al, 2005;Yi et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, previous studies on the work of social workers in the field of cancer have identified compassion fatigue, vicarious traumatization, secondary traumatic stress and burnout (Simon et al, 2005Yi et al, 2016.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations